The lies they told - Wiseman, Ellen Marie (Kensington Publishing Corp., 2025)
"In 1930s Virginia, Lena Conti, a young immigrant mother separated from her family at Ellis Island, builds a new life in the Blue Ridge Mountains but must resist a brutal eugenics campaign that targets her community and threatens to take her daughter"--